Safety aspects of steel beam subjected to combined action of bending and torsion - Bhatnagar, S. D.; Sehgal, V. K.; Gopal, Krishna (Journal of Structural Engineering, 2025)
Rolled steel joists are commonly used as beam in buildings or structures to support distributed loads that cause biaxial bending and torsion, prediction of their behavior is very difficult. This paper focuses on behavior and design of steel beam under combined bending and torsion. Advanced First Order - Second Moment (AFOSM) method was used for calculating safety index and Limit State Design (LSD) method for factor of safety for particular random variables. Different I-beams with simply supported beam configuration and with one-meter span length are tested to evaluate their flexural-torsional buckling response. The results indicate that the partial factor of safety for material comes out in the range of 1.0 to 1.3 for steel (1.1 as per IS 800:2007) and safety index in range of 2.2 to 3.80.